Pathological Vaginal Discharge among Pregnant Women: Pattern of Occurrence and Association in a Population-Based Survey - Tânia Maria M. V. da Fonseca; Juraci A. Cesar; Raúl A. Mendoza-Sassi; Elisabeth B. Schmidt (Obstetrics and Gynecology International)
This study aimed to assess the prevalence of pathological vaginal discharge and to describe risk factors associated with pregnant women. All women living in the city of Rio Grande, Southern Brazil, who gave birth in 2010 were included in the study. A standardized questionnaire was administered to collect information on demographic, reproductive, and health-related factors and morbidity during pregnancy. The chi-square test was used to compare proportions, and multivariate Poisson regression with robust variance was performed. Of the 2,395 women studied, 43% had pathological vaginal discharge during pregnancy. The adjusted analysis showed that younger women of lower socioeconomic condition, those with a past history of abortion, vaginal discharge in a previous pregnancy, and treated for depression, anemia, and urinary tract infection during their current pregnancy, were more likely to have pathological vaginal discharge. Vaginal discharge during pregnancy was highly prevalent in the sample studied calling for proper risk factor management at the primary care level.